Disseminação de programas públicos de microcrédito: o caso da região metropolitana de São Paulo - Silva, Roberto Vilela de Moura (2007)
This work analyzes the dissemination of microcredit programs implemented by municipalities in the Metropolitan Region of São Paulo, and identifies the factors that have influenced the adoption of these programs as well as the factors the have influenced the choice between different models of programs: state run and joint venture between state and private organizations. Selected cases are examined with focus on the dissemination process. This study concludes that the generalized adoption of microcredit programs in the last 15 years by municipalities was influenced by many factors: 1) the existence of common social problems and the perception of them as priorities to governments, 2) the reduction of inflation rates and the changes in the regulation of the activity, that created a better environment to the implementation of the microcredit programs; 3) the identification of microcredit as a solution to a perceived problem through the access to information of microcredit programs developed in Brazil and in other countries. However, the access to information about different microcredit programs models was influenced by the municipal technical and financial capabilities and the participation of its policy makers and bureaucrats in networks that addresses common problems and possible solutions.